Study on the Implementation and Evaluation of Management Models and Approaches to Islamic Education for Early Childhood - I. Sere, Muh Furqan; Suryana, Aep Tata; Fikri, Zaky Aizul (Eureka : Jurnal Pemikiran dan Penelitian Manajemen Pendidikan Islam, 2025)
This study discusses the implementation and evaluation of management models and approaches used in early childhood Islamic education (PIAUD). The focus of the study is on how managerial concepts are applied systematically and in accordance with the characteristics of child development. Using a qualitative literature review method, this article analyses relevant literature on management strategies and Islamic educational approaches. The results indicate that the effectiveness of management is highly dependent on the alignment of approaches with children’s needs, the role of educators, and institutional structure. Evaluation of the implementation of management models in PIAUD institutions highlights the need for continuous adaptation and innovation to achieve optimal learning outcomes. These findings are expected to contribute to the development of an Islamic values-based management system for early childhood education Keywords: Strategy, Evaluation, Early Childhood Education